Karakteristik Produk Olahan Sarabba Bubuk Instan dengan Penambahan Ketumbar (Coriandrum Sativum) Menggunakan Metode Kristalisasi - Asni, Andi; Salfiana, Salfiana; Muhanniah, Muhanniah (Agricultural Technology Education Study Program, 2024)
Sarabbba is a local drink that is known among the Bugis-Makassar community, South Sulawesi. This drink is popular with many people because it provides a refreshing effect and warms the body. Various modifications need to be made to promote this traditional drink, one of which is by adding spices such as coriander which is also recognized as having several health benefits. The various minerals found in coriander seeds (Coriandrum sativum) function as flavonoids,bone minerals,yield and help maintain proper blood pressure. The aim of this research was to determine the effect of adding coriander to instant sarabba powder on product moisture content metrics and organoleptic tests. In this study, three treatments the addition of five grams, ten grams, and fifteen grams of coriander were used three times each. ANOVA was used to evaluate research data. Duncan's multiple range test is used to ensure that there are real differences between treatments if the analysis shows that there are differences between treatments. Empirical studies show that the water content, yield and color produced are not significantly influenced by instant sarabba powder. The addition of 5 grams of coriander with an average color of 4.12, aroma of 4.11 and taste of 4.07 was the best treatment in terms of organoleptics.